Early cannulation of the Hemodialysis Reliable Outflow graft. Issue 2 (March 2020) - Vowels, Travis J; Mohamed, Ahmed; Bennett, Matthew E; Peden, Eric K
Objective: In complex dialysis patients, central venous stenosis may preclude additional upper extremity access options. The Hemodialysis Reliable Outflow graft (Merit Medical Systems, Inc.) can bypass this stenosis providing patients with an additional upper extremity long-term access option. We report our experience with early-cannulation Hemodialysis Reliable Outflow grafts and compare them to traditional Hemodialysis Reliable Outflow grafts. Methods: We retrospectively reviewed all patients undergoing Hemodialysis Reliable Outflow graft placement from 1 January 2013 through 15 August 2017 at our institution and compared those undergoing placement of traditional Hemodialysis Reliable Outflow grafts and simultaneous tunneled dialysis catheter insertion to those undergoing Hemodialysis Reliable Outflow graft placement using an early-cannulation Hemodialysis Reliable Outflow graft without a tunneled dialysis catheter. Results: A total of 88 patients had 98 Hemodialysis Reliable Outflow grafts inserted throughout this time period. Of these, 61 (62%) were early-cannulation Hemodialysis Reliable Outflow grafts, while 37 (38%) were traditional Hemodialysis Reliable Outflow grafts. Primary, primary-assisted, and secondary patency rates at 1 year were higher for the traditional Hemodialysis Reliable Outflow graft cohort (53.1% vs 25.2%, p < 0.01; 70.1% vs 30.5%, p < 0.01; and 80.4% vs 55.4%, p = 0.07, respectively). There was no difference in the rate of postoperative hematoma, seroma, pseudoaneurysm formation, steal syndrome, or overall graft thrombosis between the two cohorts. Early-cannulation Hemodialysis Reliable Outflow grafts required earlier reintervention for thrombosis and earlier reintervention for any cause when compared to traditional Hemodialysis Reliable Outflow grafts (146 ± 184 days vs 417 ± 272 days, p < 0.01, and 123 ± 169 days vs 401 ± 311 days, p < 0.01, respectively). Conclusion: In complex dialysis patients, early-cannulation Hemodialysis Reliable Outflow grafts have significantly lower 1-year primary and primary-assisted patency rates and require earlier reintervention to maintain this patency compared to traditional Hemodialysis Reliable Outflow grafts.